Analisis Elemen Visual pada Promosi Busana Muslimah di Instagram (Studi Kasus Merek Hijab Juniper Lane, Zaha, dan Zysku Xena di Bandung) - Fetrianggi, Ramadita; Mutiaz, Intan Rizky; Widiawati, Dian (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2017)
Analysis of Visual Elements on Muslimah Clothing Promotion in Instagram (Case Study on Brands of Hijab Juniper Lane, Zaha, and Zysku Xena in Bandung). Muslim clothing in the form of hijab has become popular as a religious lifestyle and identity. The popularity of hijab is due to the promotion of marketing through instagram displaying muslim fashion clothing that is designed very interesting, so that consumers become interested and marketing becomes increasing. This study aims to examine muslim clothing photos on instagram hijab with brands of Juniper Lane, Zaha, and Zysku Xena in Bandung seen from the visual elements of photography. The research method used case study with descriptive approach through visual analysis. The research subjects are instagram photos on Juniper Lane hijab brand, Zaha, and Zysku Xena in Bandung. Data collection techniques were collected by observation, instagram photo documentation study, and interviews with local brand owners of hijab and consumers. Data were analyzed by visual analysis, content analysis, and qualitative analysis. The results show that muslim clothing photos on instagram with brands of hijab Juniper Lane, Zaha, and Zysku Xena in Bandung have fulfilled the visual elements of photography, so the photo design becomes attractive, the consumers become interested in them, and the marketing becomes increasing.